2022
DOI: 10.1002/ajpa.24636
|View full text |Cite
|
Sign up to set email alerts
|

Reflections of manual labor in the hand entheses of early industrial women workers with extensively documented life histories

Abstract: ObjectivesSex‐based occupational variability constitutes a fundamental component of human behavior and a major focus of research focusing on biocultural evolution. However, the reliability of reconstructing physical activity in past women is often compromised by the lack of female skeletal collections with adequately documented lifetime occupations, domestic living conditions, medical records, and socioeconomic status. Here, we attempt to reconstruct habitual manual activity in a skeletal sample of early indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…Consequently, a PCA on raw entheseal values showed clear variation between runners and controls on the PC2 axis, which showed positive loadings for all three entheses (Figure 3). Similarly, in previous studies on extensively documented human skeletal samples (Karakostis & Hotz, 2022;Karakostis et al, 2017), the observed occupational trends were distinctive both in the size-adjusted PCA and the raw PCA.…”
Section: Principal Component Analysis (Pca)supporting
confidence: 75%
See 4 more Smart Citations
“…Consequently, a PCA on raw entheseal values showed clear variation between runners and controls on the PC2 axis, which showed positive loadings for all three entheses (Figure 3). Similarly, in previous studies on extensively documented human skeletal samples (Karakostis & Hotz, 2022;Karakostis et al, 2017), the observed occupational trends were distinctive both in the size-adjusted PCA and the raw PCA.…”
Section: Principal Component Analysis (Pca)supporting
confidence: 75%
“…In brief, the steps are the following: Development of 3D surface models (a), pseudocoloring the bone surface using the "equalize vertex colors" filter (b), pseudocoloring the bone surface by curvature based on the filter "discrete curvatures" (c), rough selection of the entheseal surface plus a thin zone of the flatter surrounding (non-entheseal) bone area (d), delineation of the exact entheseal borders after using the filter "curvature principal directions" or "calculation of geodesic distances", which highlight entheseal borders (e), cropping of the surrounding nonentheseal bone area (i.e., blue zone in panel e), and measuring entheseal surface size in mm 2 (f). More details and illustrations can be found in several previous studies (Castro et al, 2022;Karakostis et al, 2020;Karakostis & Hotz, 2022;Karakostis, Jeffery, & Harvati, 2019;Karakostis & Lorenzo, 2016). [Colour figure can be viewed at wileyonlinelibrary.com] size proxies (bone length and articular surface area size), age group, and biological sex.…”
Section: Techniques For Size Adjustmentmentioning
confidence: 99%
See 3 more Smart Citations